Strategi Humor Gibran Rakabuming dalam Komunikasi Politik di Media Sosial X (Twitter) - Rizqi Nandadita Pamungkas; Permadi, Didi; Florina, Ike Desi (Jurnal Pemerintahan dan Politik, 2024)
This research aims to analyze how the Vice President of Indonesia, Gibran Rakabuming, uses humor in political communication via the social media platform "X" (formerly known as Twitter). In a context where social media has become a primary channel for political communication, the use of humor has proven to be an effective tool for attracting public attention and shaping perceptions of political leaders. Qualitative content analysis methods were used to identify the types of humor used by Gibran, as well as its purpose and impact in a political context. Data was collected through direct observation of Gibran's uploads which were related to political communication and contained elements of humor. The research results show that Gibran uses humor for various purposes. Apart from building a positive image as a leader who is close to the people, Gibran also uses humor to convey political messages in a way that is more relaxed and easier for the public to understand. The positive response from the public to Gibran's use of humor in political communication shows its effectiveness in strengthening relations between leaders and society, as well as increasing public involvement in the political issues discussed. This research provides an in-depth understanding of how the use of humor influences public perceptions of political leaders in the digital era. Practical implications include the importance of understanding the strategic role of social media in building a positive public image and strengthening connections between leaders and their constituents through the use of humor in political communication.